Four new Planothidium species (Achnanthidiaceae, Bacillariophyceae) from the Karst region of Guizhou in China - Yun Li; Lin-Xin Lu; Hui-Wen Zhou; Pan Yu; John Patrick Kociolek; Wan-Ting Pang; Quan-Xi Wang; Qing-Min You (PhytoKeys)
Four new species of monoraphid diatoms belonging to the genus Planothidium were studied and described from the karst region of Guizhou Province, China. The morphological characteristics of these new species were observed and documented using light and scanning electron microscopy. Planothidium pseudoreichardtii sp. nov. exhibits a broad sinus at the central area on the interior of the rapheless valve, linear shallow depressions and a unique enlarged areola at the end of the striae on the exterior rapheless valve. Planothidium liboensis sp. nov. is characterized by 4–5 rows striae on both valves, a cavum at the central area on the interior rapheless valve and irregular depressions on the exterior rapheless valve. Planothidium angustirostratum sp. nov. features elliptical valves with narrowly rostrate apices, a cavum at the central area of interior rapheless valve and circular depressions on the exterior rapheless valve. Planothidium maolanensis sp. nov. has elliptical valves without protracted apices, coarsely-spaced striae on the one side of the central area of the both valves. These four new species were compared with other similar Planothidium taxa. In addition, ecological information was provided and the stability of some features was discussed.